Pengaruh Kualitas Pelayanan dan Promosi Terhadap Keputusan Pembelian KFC Secara Online Pada Mahasiswa Insitut STIAMI - Intan Iseria; Gofur Abdul (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine how much the reduction in service quality and promotion of KFC purchase decisions online at the central STIAMI Institute of Business Students 2018. In this study using descriptive quantitative approach. Primary Data used is data obtained through questionnaires. The population used is business students of Institut STIAMI Pusat class of 2018. The sample used was as many as 129 respondents using purposive sampling method. Data analysis methods used in this study are validity and reliability test, linearity test, normality, multicolonearity, heteroskedasticity, multiple linear analysis, t test, f test and coefficient of determination. The results found that: (1) the quality of Service is partially affected by 3.244 with a significant value of 0.002. (2) promotion partially effect of 6.044 with a significant value of 0.000. (3) the quality of Service and promotion simultaneously effect of 89.077 with a value of 0.000. (4) the magnitude of the influence of service quality and promotion of the purchase decision of 58.6% while the remaining 41.4% is influenced by other variables that are not done by researchers.